The Knowledge and Practice of Nurses Related to Interventional Patient Hygiene in Critical Care Unit - Mustafa, Nasira; Parveen, Kausar; Afzal, Muhammad; Hussain, Muhammad; Amir Gilani, Muhammad (International Journal of Nursing Research, 2023)
Background: Patient hygiene of intubated patients is important to the prevention of infection and patient pain. However, barrier to oral entrance and patient oral care patient hygiene have little bit interest. Aim: The aim of the study was to educate successfully new health professionals and untrained people in intensive care to use of protocols of patient hygiene in critical condition. Materials andMethods: Descriptive cross-sectional study conducted. Setting: Intensive care units (ICU’s), the 150 health professionals involved in this study. Data correlated with patient hygiene, oral care, hand hygiene, skin care, and catheterization care untrained persons in ICU given knowledge about skin care, ulcers. Untrained staff members were observed by participants before and after given knowledge about patient hygiene. Before and after survey health professionals and non-licensed staff members are observed that they improve their selves. Results: Main results derived from this those health professionals who are not following the proper way or untrained staff from zero to reach 100% result. Conclusion: Knowledge gives best to untrained and health professional’s incontinence results, hence good communication between health professionals gives good outcome.